An Alternative Design Topology for Metropolitan Area Networks - Antonius Suhartomo (Journal of ICT Research and Applications, 2012)
One of the key issues in designing a network topology is vulnerability. The vulnerability parameter measures the resistance of a network to disruption of operation  after  the  failure  of  certain  stations  or  communication  links.  One counter-measure  to address  the vulnerability of a network is edge connectivity.In this paper, a  more selective concept of edge  connectivity is introduced, called component  order  edge  connectivity  for  MAN  topology  design.  This  parameter equals the smallest number of edges that must be removed in order to ensure that the  order  of  each  component  of  the  resulting  sub -network  or  sub-graph  is  less than k.